Intermediate state representation approach to physical properties of dicationic states - Velkov, Yasen; Miteva, Tsveta; Sisourat, Nicolas; Schirmer, Jochen (The journal of chemical physics, 2011)
The second-order algebraic construction (ADC(2)) approach to the two-particle (pp) propagator, devised to compute double ionization energies and associated spectroscopic amplitudes, is reformulated and extended using the concept of intermediate state representations (ISR). The ISR formulation allows one to go beyond the general limitations inherent to the propagator approach, as here (N−2)-electron wave functions and properties become directly accessible. The (N−2)-electron ISR(2) equations for a general one-particle operator have been derived and implemented in a recent version of the double ionization ADC(2) program. As a first test of the method, the dipole moments of a series of 2h states of LiH, HF, and H2O were computed and compared to the results of a full configuration interaction (FCI) treatment. The dipole moments obtained at the ADC(2)/ISR(2) computational level are in good agreement with the FCI results.
Gesehen am 07.12.2022